Processing and surface treatments for pseudoelastic wires and strands. Issue 4 (12th March 2017) - Spriano, Silvia; Balagna, Cristina; Ferri, Ada; Dotti, Francesca; Villa, Elena; Nespoli, Adelaide; Tori, Alice
ABSTRACT: The aim of this work is a preliminary investigation of the manufacturing process of Ni-Ti and Ni-Ti-Cr wires and strands to be applied in mechanical applications. The diamond wires for stone cutting were used as a case study. A prototype of multiwire Ni-Ti strand has been prepared, characterized and thermally treated in this research. The pseudoelastic strands have not been widely investigated in the literature to date, and they are not available in the market with this size (final diameter in the 1–2 mm range). A mechanical characterization (tensile and three-point bending tests), as well as surface analysis (scanning electron microscopy [SEM], X-ray photoelectron spectroscopy [XPS], Energy Dispersive X-ray Spectrometry [EDS], dynamic wettability), of a single wire and multiwire strand was performed. Moreover, different surface treatments to be used during the manufacturing process have been tested for improving the adhesion of a polymeric coating (polyurethane) as protection against abrasion and as the binding element of the diamond beads assembled on the strand. The surfaces were treated by mechanical roughening and different chemical modifications (acid and peroxide etching) and characterized.